Why do developed economies become vulnerable to economic cycles? - Mykhailyshyn, Lilia; Vasylchenko, Serhii (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
The possible reasons for the intensification of cyclical fluctuations of the economies of the developed countries in the last decade are analyzed in the article. At the same time, the countries with risky markets (emerging markets and developing economies) are experiencing lower GDP losses during cyclical reductions of the economy. This is particularly paradoxical in view of the fact that developed economies are generally considered to be more stable and competitive. Besides, during the twentieth century, mankind has accumulated considerable experience in counteracting the cyclical nature of national economies and learned to smooth the amplitude of cyclical fluctuations. The authors of the article put forward and substantiate the assumption that the reason for the increase in the amplitude of cyclical fluctuations, increase of the depth of cyclical fluctuations of economies of the developed countries compared to the countries with emerging markets and developing economies, is the significant difference in the structure of these economies. The significant predominance of the tertiary sector in the developed economies makes them more vulnerable to cyclical fluctuations due to the greater multiplier effect that is inherent in the tertiary sector industries compared to other sectors of the economy. The conducted correlation analysis showed the presence of the strong relationship between such parameters of the economy as the share of the tertiary sector in the economy and the percentage value of the predicted economic recession in 2020 in the developed economies and emerging markets and developing economies. But it is necessary to keep in mind that the autonomous cost multiplier works in the opposite direction, accelerating the economic decline during the economic cycle. That is why, in our opinion, measures of state regulation of the economy today should be increasingly aimed at regulating the tertiary sector to prevent the increasing cyclicality of the modern global economy, as the leading economic leaders themselves are often becoming generators of the business cycle due to economic financialization and tertiary sector growth in general.